THE INFLUENCE OF ORGANIZATIONAL CULTURE AND MOTIVATION ON EMPLOYEE PERFORMANCE - Tutik Winarsih; Arif Hidayat (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The main purpose of the study is to investigate the impact of